P‐27: A Novel PWM Driving Pixel Circuit with Metal‐Oxide TFTs for MicroLED Displays. Issue 1 (28th June 2022) - Jen, Ko-Ruey; Chen, Yi-Chien; Chang, Yu-Ching; Fan, Yang-Shun; Huang, Chen-Shuo; Tang, Ying-Hsuan; Chiang, Chia-Wei; Huang, Po-Jui; Lim, Kai-Chuin; Chen, Chih-Cheng; Chen, Yung-Chih; Chen, Kuo-Kuang
Abstract : A pixel circuit for micro‐LED display has been developed with IGZO TFT device. By using pulse width modulation method, the pixel circuit can operate at high peak current and low duty ratio to keep micro‐LED at high emission efficiency and stable color performance.